2022
DOI: 10.32677/ijch.2017.v04.i02.018
|View full text |Cite
|
Sign up to set email alerts
|

Scrub typhus in children: Clinical profile and complications at a Tertiary Care Teaching Hospital in Uttarakhand

Abstract: Background: Scrub typhus is an acute febrile illness caused by rickettsia Orientia tsutsugamushi. Rickettsial infections are grossly underdiagnosed in India because of their non-specific clinical presentation, low index of suspicion among clinicians, and lack of diagnostic facilities. Objective: Objective of the study is to study the clinical profile, complications, and outcome of pediatric scrub typhus. Materials and Methods: This prospective observational study was conducted in the Department of Pediatrics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 26 publications
2
5
1
Order By: Relevance
“…11 AKI as a complication is observed in various studies with a range between 2% and 20% and in our study it was 14%. 11,17,26,27 In our study, one case of hemophagocytic lymphohistiocytosis (HLH) was found similar to a study done by Khandelwal et al 17 In the study done by Sankhyan et al three cases (20%) of HLH were diagnosed out of which one child died. 28 In our study, the mainstay of antibiotics was oral doxycycline and intravenous chloramphenicol.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…11 AKI as a complication is observed in various studies with a range between 2% and 20% and in our study it was 14%. 11,17,26,27 In our study, one case of hemophagocytic lymphohistiocytosis (HLH) was found similar to a study done by Khandelwal et al 17 In the study done by Sankhyan et al three cases (20%) of HLH were diagnosed out of which one child died. 28 In our study, the mainstay of antibiotics was oral doxycycline and intravenous chloramphenicol.…”
Section: Discussionsupporting
confidence: 89%
“…Thrombocytopenia was detected between 20 and 88% in various studies but in our study it was 52%. 17,25,27,30 Leukopenia was uncommon in our study being around 3.6% whereas it was seen in 23% of the patients in another study. 17 Leukocytosis was seen in 39.2% which is almost the same as that seen in other studies ranging from 21-47%.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations